2010
DOI: 10.1111/j.1365-3180.2010.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving weed management in organic spring barley: physical weed control vs. interspecific competition

Abstract: Few options exist for effectively managing weeds in organic spring cereals. Establishing a competitive crop through increased seeding rate provides improved weed suppression, but competition with inter-row weeds is delayed, compared with an alternative, more uniform spatial pattern of sowing. We speculated that (i) enhanced interspecific competition or (ii) improved physical weed control with a strategy of wide-row sowing and inter-row hoeing would both provide better weed control than current regional organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
4
43
1
Order By: Relevance
“…One of the causes must be related to the rapid canopy closure between the rows by maize plants, in reduced spacing and in high population, struggling the germination and growth of weeds between the rows of the maize crop. The results described here are in agreement with those obtained by Kolb, Gallandt, and Molloy (2010). They studied physical weed control versus interspecific competition in organic spring barley and found improvements with respect to weed control at wide row strategy.…”
Section: Discussionsupporting
confidence: 91%
“…One of the causes must be related to the rapid canopy closure between the rows by maize plants, in reduced spacing and in high population, struggling the germination and growth of weeds between the rows of the maize crop. The results described here are in agreement with those obtained by Kolb, Gallandt, and Molloy (2010). They studied physical weed control versus interspecific competition in organic spring barley and found improvements with respect to weed control at wide row strategy.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, measures promoting crop competition, as well as reliance on physical weed control should be emphasized in organic cropping (Kolb et al 2010). For instance, the abundance of E. repens in organic cropping is a cause for some concern and calls for improved control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In weed-crop competition, availability of resources (water, nutrients, and space) and environmental factors like light and temperature affect the extent of the competition (Kropff et al, 1993;Weiner et al, 2001;Guillemin et al, 2013). Studies with a number of crops like wheat (Kristensen et al, 2008;Mashingaidze et al, 2009), rice (Chauhan and Johnson, 2010a;Khaliq et al, 2014a,b), barley (Kolb et al, 2010), cotton (Reddy, 2001), millet (Shinggu et al, 2009), sorghum (Grichar et al, 2004), and soybean (Hock et al, 2006), have shown inverse relationships between narrow crop rows and weed growth. Although wider crop rows facilitate weed control by intercultural operations, weed growth in wheat is usually suppressed by narrow row spacing (Shrestha and Fidelibus, 2005).…”
Section: Introductionmentioning
confidence: 97%